Kaidah Sadd Al-Dzari’ah dan Fathu Al-Dzari’ah sebagai Dasar Larangan Penjaminan Modal dalam Akad Mudhârabah - Wiraputra, Jhody; Bahrudin, Moh.; Hilal, Syamsul (STAI Al Musaddadiyah Garut, 2025)
This study critically and comparatively analyzes the justification for the prohibition and exception of capital guarantees in the Mudhârabah contract—an essential profit-sharing instrument in Islamic economics that functions as a contract of trust (akad amanah). Fundamentally, Mudhârabah requires the capital owner (shahibul māl) to bear the full risk of business loss. The absolute prohibition of capital guarantees by the manager (mudhārib) is strictly emphasized through the legal maxim Sadd al-Dzarī‘ah, as an implicit guarantee clause alters the essence of the profit-sharing partnership into an interest-bearing loan, which constitutes riba. However, in the context of contemporary Islamic finance, the need for asset protection as part of Maqāṣid al-Sharī‘ah allows for limited exceptions based on the principle of Fath al-Dzari‘ah, which permits liability for compensation only in cases of gross negligence or misconduct. The findings reveal that the principles of Sadd and Fath al-Dzari‘ah operate harmoniously as complementary mechanisms—the former preserving the integrity of the contract from usurious practices, and the latter ensuring institutional efficiency and sustainability by mitigating ethical risks—thereby enabling Mudhârabah to function fairly and securely in the modern market. Keywords: Fath al-Dzari‘ah, Mudharabah, Sadd al-Dzari‘ah